The Effect of Mindfulness Based Stress Reduction (MBSR) on Psychological Distress in Coronary Artery DISEASE (CAD) Patients after Coronary Artery Bypass Grafting (CABG) - Desy Setiawati; Wati Jumaiyah; Dhea Natashia; Yani Sofiani (GLOBAL HEALTH SCIENCE GROUP, 2026)
Coronary artery disease (CAD) patients undergoing preventive coronary artery bypass graft (CABG) surgery commonly experience psychological distress in the form of anxiety, stress, and depression, which can hinder the recovery process. Mindfulness-Based Stress Reduction (MBSR) programs are known to be effective in reducing psychological burden in various chronic disease conditions, but research in the CHD population after preventive CABG is limited. Objective to determine the effect of a mindfulness-based stress reduction (MBSR) intervention on psychological distress in CHD patients undergoing preventive CABG. The study used a true-experimental design. The sample consisted of CHD patients who met the inclusion criteria, divided into intervention and control groups. The intervention group participated in the MBSR program for 21 days, while the control group received standard care. A total of 12 respondents participated. Stress, anxiety, and depression levels were measured using standardized instruments such as the Hospital Anxiety and Depression Scale (HADS) instrument, the level of stress using the Perceived Stress Scale (PSS) instrument. Data analysis was performed using bivariate paired t-tests and multivariate. The MBSR program demonstrated a significant reduction in stress, anxiety, and depression levels in the intervention group compared to the control group (p < 0.05). The difference in mean psychological scores before and after the intervention indicated a greater improvement in mental well-being in MBSR participants. The MBSR intervention was effective in reducing psychological distress in coronary artery disease patients after CABG prevention.